Empowering employers to address domestic violence and its impact on the workplace - Adriana Marques Silva; Joaquim Pinto Contreiras; Ana Patricia Duarte (Tourism & Management Studies)
Domestic violence affects all social and economic classes and age groups, but this type of public crime has traditionally not been linked to the workplace. This study sought to provide a new perspective on domestic violence by focusing on how it can be addressed in work contexts. Qualitative research was conducted based on a focus group to clarify what companies in Portugal's Algarve region know about this crime and its repercussions for the workplace. The results include recurring themes, such as domestic violence as a taboo subject, the difficulty of detecting this crime at work despite extant well-established indicators of this problem, its repercussions for teams, unawareness of specifically related labour laws and the need to train and inform workers. The findings also cover two emerging topics – corporate social responsibility and occupational health – as intervention areas. Given these results, an action plan was developed to be implemented in organisations in order to provide support to employees who are domestic violence victims.